DISTRIBUTION AND IDENTIFICATION OF FRUIT FLIES (DIPTERA: TEPHRITIDAE) ATTRACTED ON METHYL EUGANOL AND CUE LURE IN CENTRAL BANGKA REGENCY, BANGKA BELITUNG - Saputra, Herry Marta; Afriyansyah, Budi (Universitas Lampung, 2021)
Distribution and identification of fruit flies (Diptera: Tephritidae) attracted on methyl euganol and cue lure in CentralBangka Regency, Bangka Belitung. Not all fruit flies species of Dacini tribe were pests to fruit and fleshy vegetables. CentralBangka Regency is one of the citrus producer in the Bangka Belitung Islands Province. Information about this fruit flies in thisarea was limited. This study aimed to make inventory and identification of fruit flies species of the Dacini tribe in CentralBangka Regency, Bangka Belitung. The research was conducted in Nibung, Penyak, and Terentang Villages in Central BangkaRegency, Bangka Islands. Lynfield traps were installed in a citrus cultivation area about 1.5 m above ground level. Lynfieldtraps were treated with the attractant and deltamethrin (2: 1; v / v) on dental cotton. Methyl eugenol and cue lure were usedto attract the male fruit flies. In Central Bangka Regency, 3 genera and 14 species of fruit flies were obtained from the tribeDacini. The fruit fly species of Bactrocera atrifemur, B. carambolae, B. dorsalis, B. occipitalis, and B. umbrosa were caughtin the methyl eugenol attractant trap. Meanwhile, the fruit fly species of B. albistrigata, B. fuscitibia, B. melastomatos,B. neocognata, B. nigrotibialis, Dacus nanggalae, Zeugodacus apicalis, Z. caudatus, and Z. cucurbitae were caught in thecue lure attractant trap. The fruit flies obtained from the two different attractants were used to develop dichotomous keys.